'What does an O say when there's no E at the end?' Parents' reading‐related knowledge and feedback during child‐to‐parent reading. (13th March 2019) - Segal, Aviva; Martin‐Chang, Sandra
Abstract : Background: Although a large body of research has investigated teachers' reading‐related knowledge and associated pedagogical practices, comparatively little is known about these factors in parents. Therefore, the present study examined the association between parental reading‐related knowledge and feedback during child‐to‐parent reading. Methods: Seventy parents completed a reading‐related knowledge questionnaire (phonological segmentation, knowledge of written syllable patterns, identification of regular and irregular word spellings) while their 6 and 7‐year‐old children were administered the Peabody Picture Vocabulary Test and the reading subtest of the Wide Range Achievement Test–Fourth Edition. Based on children's Wide Range Achievement Test–Fourth Edition reading performances, they were assigned one of five adapted passages from the Gray Oral Reading Test–Fifth Edition to read aloud to their parents; parents were asked to help as they normally would. Reading sessions were videotaped; the content was transcribed and coded for evidence of verbal and nonverbal parental feedback (evaluative feedback: praise and criticism; miscue feedback: graphophonemic, context cues, try again, terminal and ignoring miscues). Results: Consistent with the teacher and parent literature, reading‐related knowledge was positively associated with children's reading scores. Parents' reading‐related knowledge additionally accounted for unique variance in praise and graphophonemic feedback during child‐to‐parent reading beyond the variance already explained by children's reading scores. Conclusions: These findings suggest that even after accounting for children's reading abilities, reading‐related knowledge contributes to a positive affective atmosphere for teaching key literacy skills to young readers. Implications are discussed in terms of enhancing parents' reading‐related knowledge and associated practices in hopes of positively contributing to children's literacy outcomes. Highlights: What is already known about this topic Teachers' reading‐related knowledge significantly predicts the instruction they provide and students' reading development. Consistent with the teacher research, parents' reading‐related knowledge is associated with children's reading performances. Parents tend to be quite positive and not critical when jointly reading with their children (Martin‐Chang & Gould, 2012). What this paper adds Here, we see the contribution of parents' feedback practices and their associations with parents' reading‐related knowledge and children's reading scores. Parents' reading‐related knowledge contributes to the affective atmosphere of joint reading. Parents' reading‐related knowledge accounts for more attempts at making explicit grapheme–phoneme connections (reading instruction) when jointly reading with their emergent readers. Implications for theory, policy or practice To direct parents towards available websites to improve their reading‐related knowledge. To develop parents' and teachers' reading‐related knowledge through joint parent/teacher learning evenings and other such efforts. Much of the initiatives to date have spoken to the importance of reading to children; however, the contributions of children reading to their parents need further attention.